Estimation Error in Income Determination: A Comment. - Keys, David E.; Norton, Curtis (The Accounting Review, 1978)
Confidence interval financial statements have been suggested as a means to convey the uncertainty surrounding the items on the financial statements. Albrecht [1976] provided a conceptual framework within which the uncertainty of income statement items can be computed and then illustrated the degree of uncertainty that existed in one firm's earnings computations. This article further develops Albrecht's conceptual framework by discussing types of accounting error, the methods of quantifying accounting error, the period(s) used to derive the distribution on accounting error and the level of aggregation at which accounting error is quantified.